Social acceptance to geothermal development in Indonesia - Paulus Wirutomo, Hariyadi,; S. Witoro Sularno, Setyo S. Moersidik, (Opción, 2019)
This article examines the relationship between the strengthening quality of socio-cultural life elements (SCL) and the issue of social acceptance to geothermal power plant (GPP) development, focusing on the GPP project in Baturraden, Central Java, Indonesia. This study uses a qualitative approach with the data collection method based on the results of the survey and SEM analysis. As a result, the mission of creating a balance in economic, environmental, and social interests as understood in a sustainable development paradigm becomes a necessity. In conclusion, through the co-existential state engagement, social support in the GPP development will be more easily achieved.